Studies on mealybugs (Hemiptera: Pseudococcidae) in Indonesia, with description of a new species and three new country records - Zarkani, Agustin; Ercan, Cansu; Apriyanto, Dwinardi; Kaydan, Mehmet Bora (Zootaxa, 2023)
Pseudococcid mealybugs (Hemiptera: Coccomorpha: Pseudococcidae) include economically important insect pests worldwide; however, little is known about the species present in Indonesia. Samples were collected and identified from wild and cultivated plants in several regions of southern Sumatra, Indonesia between 2018 and 2020. Eighteen species of Pseudococcidae in 8 genera were identified, including one undescribed species and new host plants. Dysmicoccus zeynepae Zarkani & Kaydan sp. n. is described and illustrated based on the morphology of the adult female, and a key is provided for the identification of all 18 species. Furthermore, Dysmicoccus arachidis Williams, D. carens Williams and Pseudococcus leptotrichotus Williams are recorded for the first time from Indonesia; new locality and host-plant data are given for these species.